Correlation of environmental management and intensification of wastewater treatment in the context of ensuring environmental safety of machine building enterprises - Bosiuk, A.; Shestopalov, O.; Sacun, A.; Tykhomyrova, T. S.; Kulinich, S. (Видавничий дім "Гельветика", 2024)
The article examines the correlation between environmental management and the intensification of wastewater treatment, which is an important aspect of ensuring the environmental safety of a machine-building enterprise. Therefore, it is important to develop and implement an effective environmental management system, which includes pollution monitoring, planning measures to minimize emissions and discharges, and the implementation of environmentally friendly technologies. The purpose of the work is to analyze and study the relationship between environmental management and the intensification of wastewater treatment and to develop recommendations for improving the efficiency of environmental management and wastewater treatment. The successful solution of these issues helped to develop an effective wastewater management strategy, increase the efficiency of wastewater treatment and reduce its costs, and also ensured the fulfillment of environmental standards and legal requirements, as a result of which significant results were achieved to improve environmental safety at the enterprise and to reduce the negative impact on the environment. In the study of this correlation, there are several aspects that have scientific novelty: the use of new methods of intensification of wastewater treatment; studying the impact of environmental management on the efficiency of wastewater treatment and developing ecommendations for improving the effectiveness of environmental management and wastewater treatment. The study in this field is important from both scientific and practical points of view. The implementation of environmental policy has a positive effect on the image of the enterprise, increases its competitiveness and ensures sustainable development. In addition, it promotes compliance with high standards of sustainable development, which is an important prerequisite for attracting new investments and market advantages.

У статті розглянуто питання взаємозв’язку між екологічним менеджментом та інтенсифікацією очистки стоків, яке є важливим аспектом забезпечення екологічної безпеки машинобудівного підприємства. Тому важливо розробити та впровадити ефективну систему екологічного менеджменту, яка містить у собі моніторинг за забрудненням, планування заходів з мінімізації викидів та скидів, впровадження екологічно чистих технологій. Мета роботи полягає в аналізі та вивченні взаємозв’язку між екологічним менеджментом та інтенсифікацією очищення стоків та розробці рекомендацій щодо покращення ефективності екологічного менеджменту та очищення стоків, успішне вирішення цих питань допомогло розробити ефективну стратегію управління стічними водами, підвищити ефективність очи щення стічних вод та зменшити витрати на їх очищення, а також забезпечило виконання екологічних нормативів та вимог законодавства, в результаті чого було досягнуто значних результатів для підвищення екологічної безпеки на підприємстві та зменшено негативний вплив на навколишнє середовище. У вивченні цього взаємозв’язку є декілька аспектів, які мають наукову новизну: використання нових методів інтенсифікації очистки стоків; вивчення впливу екологічного менеджменту на ефективність очистки стоків та розробка рекомендацій щодо покращення ефективності екологічного менеджменту та очищення стоків. Дослідження даного напряму важливе як з наукової, так і з практичної точки зору. Реалізація екологічної політики має позитивний вплив на імідж підприємства, збільшує його конкурентоспроможність та забезпечує сталий розвиток. Крім того, це сприяє відповідності високим стандартам сталого розвитку, що є важливою передумовою для приваблення нових інвестицій та ринкових переваг.
Взаємозв’язок екологічного менеджменту та інтенсифікації очистки стоків у контексті забезпечення екологічної безпеки машинобудівного підприємства
Keywords: machine-building complex; strategy; sustainable development; environmental policy; environment; pollutants; effluents; машинобудівний комплекс; стратегія; сталий розвиток; екологічна політика; навколишнє середовище; забруднюючі речовини; стоки